OPPORTUNITIES OF USING CARTOGRAPHIC METHODS IN TEACHING BIOLOGY IN HIGHER EDUCATION. - Jololdinov Asror Toshtemirovich; Samijonova Gulzira Esonboy qizi (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract: The integration of interdisciplinary approaches in higher education is pivotal  for  enhancing  the  quality  of  biological  sciences  instruction.  This  article explores  the  significant  yet  underutilized  opportunities  presented  by  cartographic methods—the science and technology of making and using maps—in teaching biology at  the  university  level.  The  modern  biological  sciences,  encompassing  ecology, genetics, anatomy, and biogeography, are inherently spatial disciplines. Cartographic techniques, particularly  Geographic  Information  Systems  (GIS), thematic  mapping, and  geovisualization,  provide  powerful  tools  to  visualize,  analyze,  and  interpret complex biological data. This paper analyzes the didactic potential of these methods for improving spatial thinking, fostering interdisciplinary understanding, and engaging students in active, research-based learning. The analysis concludes that the strategic implementation of cartographic tools can transform biology education from a static, fact-based discipline into a dynamic, analytical, and problem-solving oriented field, thereby  preparing  students  for  the  challenges  of  modern  scientific  research  and environmental management.